Challenges and Coping Strategies of Secondary School Teachers’ Multilingual Classrooms with Tharu Students - Jora, Man Bahadur; Basnet, Hom Bahadur (Rupantaran: A Multidisciplinary Journal, 2026)
This study investigates the strategies and challenges encountered by secondary-level English language teachers in multilingual classrooms in Kailari Rural Municipality, Kailali, Nepal. Utilizing a qualitative case study design, data were collected through deep interviews and classroom observations with five secondary-level teachers. The findings have revealed significant challenges, including the management of instructional materials for diverse linguistic groups, low learner motivation, difficulties in selecting a medium of instruction, and the complexities of mixed-ability classrooms. Conversely, the study has identified effective strategies employed by teachers, such as meticulous lesson planning, the integration of Information and Communication Technology (ICT), the use of body language, and the judicious application of students’ mother tongues to facilitate comprehension. The research has concluded that successful multilingual pedagogy requires teacher flexibility, institutional support, and context-sensitive policies.